Nutritional Improvement of Gluten-Free Breadsticks by Olive Cake Addition and Sourdough Fermentation: How Texture, Sensory, and Aromatic Profile Were Affected? - Caponio, Giusy Rita; Difonzo, Graziana; de Gennaro, Giuditta; Calasso, Maria; De Angelis, Maria; Pasqualone, Antonella (Frontiers in Nutrition, 2022)
There is a growing need for gluten-free bakery products with an improved nutritional profile. Currently, gluten-free baked goods deliver low protein, fiber, and mineral content and elevated predicted glycemic index (pGI). Olive cake (OC), a by-product from virgin olive oil extraction, is an excellent natural source of unsaturated fatty acids, dietary fiber and bioactive molecules, including polyphenols and tocopherols. In this framework, this study aimed at using two selected lactic acid bacteria and a yeast for increasing the antioxidant features and the phenol profile of the gluten-free breadsticks fortified with OC, with the perspective of producing a functional food. Control (CTR) samples were prepared and compared with fermented ones (fCTR) and with samples added with either non fermented OC (nfOC) or fermented for 12 and 20 hours (fOC-12 and fOC-20). Our results showed that the predicted glycemic index (pGI) was influenced by both OC addition and sourdough fermentation. In fact, the lowest value of pGI was found in fOC-12, and hydrolysis index and pGI values of samples with OC (fOC-12 and nfOC) were statistically lower than fCTR. Both OC addition and fermentation improved total phenol content and antioxidant activity of breadsticks. Anyway, the most pronounced increase in hardness values was observed in the samples subjected to sourdough fermentation as evidenced both from texture profile analysis and sensory evaluation. Moreover, in most cases the concentration of the detected volatile compounds was reduced by fermentation. Our work highlights the potential of OC to be upcycled, in combination with fermentation, to produce gluten-free breadsticks with improved nutritional profile, although additional trials are required to enhance textural and sensory profile.